Nanogel activity of java bark extract (lannea coromandelica (houtt.) merr.) as wound healing in diabetic rats - Jumaldi Syamsy Salsabilla Riasty Putri; Nafilah Arta Dwi; Sibadu Annisa Awalia Rahma MH; Febriansyah M. Chandra; Widyaningsih Wahyu; Yuliani Sapto (BIO Web of Conferences)
Java bark ( Lannea coromandelica (Houtt.) Merr.) is used traditionally to heal wounds. In this research, nanogel made from Javanese wood bark extract (EKBKJ) was tested to see its ability to heal wounds in diabetic mice. EKBKJ nanogels were made in three different concentrations: 1%, 4%, and 7%, and tested to see their physical properties such as particle size, pH, dispersing ability, and adhesiveness. The EKBKJ nanogel activity test was carried out on six groups of mice for 14 days by monitoring the level of wound healing and visual appearance of the wound. The results showed that the three types of EKBKJ nanogel met nanogel quality standards, with 1%, 4%, and 7% nanogel able to heal wounds better than gel base in diabetic mice (p<0.05). Furthermore, 1% EKBKJ nanogel showed significantly higher healing rate compared with 4% and 7% EKBKJ nanogel. Thus, it can be concluded that 1% EKBKJ nanogel has a better effect on healing diabetic wounds.